ANCA-Associated Vasculitic Neuropathy: A Case Report - Jakiševaitė, M.; Navickaitė, I.; Žemgulytė, G. (Neurologijos seminarai, 2023)
Anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitides (AAVs) are a group of autoimmune diseases that can affect many vital organs and tissues, as well as the nervous system. When peripheral nerves are affected, one of the clinical features of AAVs can be vasculitic neuropathies (VNs). This usually causes asymmetric weakness and numbness in the distal parts of extremities, frequently followed by pain. Nerve conduction study (NCS) reveals axonal loss in multiple individual nerves, whereas a length-dependent process may also be observed. As AAV is a rare diagnostic entity and can manifest with a vast variety of symptoms, it is seldom involved in the initial diagnostic work-up of polyneuropathy. Moreover, the only definitive diagnostic method for VN is peripheral nerve biopsy. Therefore, AAV represents one of the greatest difficulties in the differential diagnosis of neuropathies. In this article, we present a clinical case of a 73-year-old patient admitted to the hospital due to blurry vision, headache, and limb weakness. The findings of the neurological examination were consistent with polyneuropathy. A thorough examination was performed to determine the exact diagnosis. However, due to the lack of typical symptoms, VN was diagnosed only after acute renal failure evolved. This case demonstrates the many symptoms that AAV can present with and the importance of a thorough differential diagnosis for multiple mononeuropathies.
Keywords: ANCA-associated vasculitis; microscopic polyangiitis; multiple mononeuropathies; vasculitic neuropathies